Platelet-Derived Microparticles (MPs) and Thrombin Generation Velocity in Deep Vein Thrombosis (DVT): Results of a Case–Control Study - Signorelli, Salvatore Santo (Vasc Health Risk Manag, 2020)
INTRODUCTION: The role of platelets (Ps) and platelet-derived microparticles (MPs) in venous thromboembolism (VTE) is still being debated. METHODS: We measured MPs, velocity of thrombin formation (PiCT) and phospholipid generation (PLPs) in 40 patients with unprovoked deep vein thrombosis (DVT), who were compared with 40 healthy controls. RESULTS: MPs were higher in DVT (7.12 nM; 25th–75th percentile 5.26–9.12) than in controls (5.45 nM; 25th–75th percentile 1.67–8.96) (p = 0.19). PiCT velocity was lower in DVT (1.87 sec; 25th–75th percentile 1.75–1.93 sec) compared with controls (1.95 sec; 25th–75th percentile 1.84–2.24 sec) (p = 0.04). PLPs were higher in DVT (77.03 µg/mL; 25th–75th percentile 72.12–103.59 µg/mL) compared with controls (68.65 µg/mL, 25th–75th percentile 55.31–78.20 µg/mL) (p = 0.02). DISCUSSION: We hypothesize that MPs could be integrated with the lab network assay in evaluating Ps’ role as an activated procoagulative condition. We encourage research on Ps and P-derived microvesicle pathways in patients with unprovoked DVT and not only in patients with cancer-induced DVT.